Quantification of training and competition load across a season in an elite australian football club - Ritchie, D.; Hopkins, W. G.; Buchheit, M.; Cordy, J.; Bartlett, J. D. (International Journal of Sports Physiology and Performance, 2016)
Purpose: Load monitoring in Australian football (AF) has been widely adopted, yet team-sport periodization strategies are relatively unknown. The authors aimed to quantify training and competition load across a season in an elite AF team, using rating of perceived exertion (RPE) and GPS tracking.